2002
DOI: 10.1128/jcm.40.4.1181-1187.2002
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure and Genetic Diversity of Actinobacillus actinomycetemcomitans Strains Isolated from Localized Juvenile Periodontitis Patients

Abstract: The phylogeny of 20 Actinobacillus actinomycetemcomitans strains isolated from patients with localized juvenile periodontitis (LJP) was investigated by using partial sequence analysis of 16S rRNA genes, arbitrarily primed PCR (AP-PCR), and four additional PCR assays that amplified polymorphic regions in the leukotoxin (lkt), cytolethal distending toxin (cdt), major fimbrial subunit (flp-1), and serotype-specific O polysaccharide gene clusters. Our analysis also included four strains isolated from healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
2
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 41 publications
4
112
2
10
Order By: Relevance
“…In a recent study (Haubek et al, 2008) in Morocco, individuals who harbored the JP2 strains had significantly increased risk of periodontal attachment loss than those with the 652 strains. However, minimally leukotoxic strains are also found in persons with LAP (Kaplan et al, 2002;Fine et al, 2007). Fine et al (2007) studied adolescents in Newark, NJ, and found that the majority of individuals who developed bone loss did not harbor the JP2 strain in their mouths during the study period.…”
Section: Relevance To Diseasementioning
confidence: 99%
“…In a recent study (Haubek et al, 2008) in Morocco, individuals who harbored the JP2 strains had significantly increased risk of periodontal attachment loss than those with the 652 strains. However, minimally leukotoxic strains are also found in persons with LAP (Kaplan et al, 2002;Fine et al, 2007). Fine et al (2007) studied adolescents in Newark, NJ, and found that the majority of individuals who developed bone loss did not harbor the JP2 strain in their mouths during the study period.…”
Section: Relevance To Diseasementioning
confidence: 99%
“…To confirm that ltxA synthesis is not affected by iron, we determined the levels of ltxA mRNA produced under normal and excess-iron growth conditions by quantitative real-time PCR (qRT-PCR) using a quantitative RT-PCR ReadyMix kit according to the manufacturer's protocol (Sigma, St. Louis, MO) ( Table 1). Highly leukotoxic strains JP2 (36,41) and NJ4500, a fresh clinical isolate (9,21), were grown in AAGM broth with and without 300 M FeCl 3 . Relative to the expression of housekeeping genes glyA (29) and gapdh (34) ( Table 1), we found that the ratio of ltxA mRNA levels under excess-iron conditions to those under normal growth conditions was approximately 1 ( Table 2).…”
mentioning
confidence: 99%
“…Molecular genetics has demonstrated a degree of biodiversity in the oral microflora and A. actinomycetemcomitans is genetically heterogeneous and comprises distinct clonal lineages that may have different virulence potentials (Kittichotirat et al, 2011). Seven serotypes have been identified among A. actinomycetemcomitans isolates; each serotype represents a distinct clonal lineage (Kaplan et al, 2002;Kilian et al, 2006;Takada et. al., 2010).…”
Section: Genetic Characteristics Of Aggregatibacter Actinomycetemcomimentioning
confidence: 99%